2016
DOI: 10.5821/sibb.24.1.5195
|View full text |Cite
|
Sign up to set email alerts
|

Sensor impedimétrico para la detección de bacterias patogénicas mediante péptidos antimicrobianos

Abstract: Áccesit Congreso SIBB 2015La peri-implantitis, una inflamación causada por la formación del biofilm, es una de las causas más importantes de la fallida de los implantes en odontología. Por esto, la detección de bacterias patogénicas al inicio del proceso de formación de biofilms, representa una estrategia muy potente para la prevención de las infecciones en los implantes. Entre los diferentes métodos para la detección de bacterias patogénicas, los biosensores electroquímicos, especialmente los sistemas basados… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The authors report that the biosensor obtained is capable of selectively detecting Salmonella spp cells with a detection limit of 15 CFU/mL. On the other hand, Hoyos, et al reported the design of an impedimetric sensor based on antimicrobial peptides for the early detection of periodontopathogenic bacteria [21]. The system is able to detect S. sanguinis in 1 h with LOD of 10 CFU/mL in KCl and 100 CFU/mL in artificial saliva.…”
Section: Evaluation Of the Biosensor Towards Detection Of E Coli 241 Evaluation Of The Linear Response Range Of The Biosensormentioning
confidence: 99%
See 1 more Smart Citation
“…The authors report that the biosensor obtained is capable of selectively detecting Salmonella spp cells with a detection limit of 15 CFU/mL. On the other hand, Hoyos, et al reported the design of an impedimetric sensor based on antimicrobial peptides for the early detection of periodontopathogenic bacteria [21]. The system is able to detect S. sanguinis in 1 h with LOD of 10 CFU/mL in KCl and 100 CFU/mL in artificial saliva.…”
Section: Evaluation Of the Biosensor Towards Detection Of E Coli 241 Evaluation Of The Linear Response Range Of The Biosensormentioning
confidence: 99%
“…Recently, peptide-based biosensors have been widely studied in pathogen detection and disease diagnosis due to their sensitivity, low cost, and specificity [18][19][20][21][22]. These devices are probably the most versatile systems due to the physicochemical properties of the peptides.…”
Section: Introductionmentioning
confidence: 99%